Dupilumab is effective in type 2‐high asthma patients receiving high‐dose inhaled corticosteroids at baseline. Issue 1 (21st October 2020) - Bourdin, Arnaud; Papi, Alberto A.; Corren, Jonathan; Virchow, J. Christian; Rice, Megan S.; Deniz, Yamo; Djandji, Michel; Rowe, Paul; Pavord, Ian D.
Abstract: Background: Dupilumab blocks the shared receptor component for interleukin (IL)‐4/IL‐13, key drivers of type 2 inflammation. In phase 2b (NCT01854047) and phase 3 LIBERTY ASTHMA QUEST (NCT02414854), add‐on dupilumab 200/300 mg every 2 weeks (q2w) reduced severe exacerbations, improved prebronchodilator (pre‐BD) forced expiratory volume in 1 second (FEV1 ) and quality of life measures, and it was generally well tolerated in patients with uncontrolled, persistent (phase 2b), or moderate‐to‐severe (phase 3) asthma. Methods: In patients on high‐dose inhaled corticosteroids (ICS) with type 2‐high asthma (subgroups including baseline blood eosinophils ≥150/300 cells/µL and/or fractional exhaled nitric oxide [FeNO] ≥25 ppb), annualized severe exacerbation rates over the treatment period, changes from baseline in pre‐BD FEV1 and asthma control (5‐item asthma control questionnaire [ACQ‐5]) were analyzed. Results: In high‐dose ICS type 2‐high subgroups, dupilumab 200/300 mg q2w vs placebo in the phase 2b (24 weeks) and phase 3 (52 weeks) studies significantly reduced severe exacerbations by 55%‐69%/57%‐60% (all P <.05) and 53%‐69%/48%‐66% (all P  < .001), respectively, except in patients with ≥ 300 eosinophils/µL in phase 2b study (24%/50% ( P  = .52/0.15). Across subgroups, pre‐BD FEV1 improved by 0.18‐0.22 L/0.19‐0.24 L (all P  < .05) and 0.23‐0.36 L/0.15‐0.25 L (all P  < .01) and ACQ‐5 scores were reduced by 0.46‐0.55/0.47‐0.85 (all P  < .05) and 0.38‐0.50/0.24‐0.30 (all P  < .05), respectively, except dupilumab 200 mg q2w in phase 2b in patients with FeNO ≥ 25 ppb (0.41; P  = .09). Dupilumab was also effective in patients taking medium‐dose ICS. Conclusion: Dupilumab significantly reduced severe exacerbations and improved lung function and asthma control in patients with type 2‐high asthma on high‐dose ICS at baseline. Abstract : This study examines dupilumab efficacy in type 2‐high asthma patients receiving high‐dose ICS at baseline. Dupilumab reduces severe exacerbations, improves lung function and asthma control in patients on high‐dose ICS with elevated baseline blood eosinophils or FeNO. Dupilumab efficacy is rapid and sustained throughout treatment and comparable across type 2‐high asthma patients receiving high‐dose ICS at baseline. Abbreviations: ACQ‐5, 5‐item Asthma Control Questionnaire; FeNO, fractional exhaled nitric oxide; FEV1, forced expiratory volume in 1 second; ICS, inhaled corticosteroids; ppb, parts per billion; pre‐BD, prebronchodilator.